FACTORS OF PROFESSIONAL ASPIRATIONS IN SOCIALLY DISADVANTAGED PUPILS OF BASIC SCHOOLS - FRIEDMANN, Zdenek (Trends in education, 2012)
The paper presents selected results of a qualitative investigation (semi-structured interviews), conducted at the beginning of 2012 in selected pupils with a social disadvantage. 98 pupils were addressed in the investigation to reveal some of the factors with a significant influence on pupils extasciiacute own professional aspirations and consequently on the choice of school or profession. The research was conducted within a research project of the Ministry of Education, Youth and Sports MSM 0021622443 called Special needs of pupils in the context of the Framework Education Programme for basic education.
Keywords: pupils with a social disadvantage; children extasciiacutes interests; professional aspirations; preparation for professional choice.